Leptin and Gestational Diabetes Mellitus - Guádix, Pilar (2019)
Emerging research has highlighted the importance of leptin in fetal growth anddevelopment, independent of its essential role in the regulation of feeding andenergy metabolism. Leptin is now considered an important signaling molecule ofthe reproductive system, since it regulates the production of gonadotropins, theblastocyst formation and implantation, the normal placentation, as well as the feto-placental communication. Placental leptin is an important cytokine which regulatesplacental functions in an autocrine or paracrine manner. Leptin seems to play acrucial role during the first stages of pregnancy as it modulates critical processes likeproliferation, protein synthesis, invasion, and apoptosis in placental cells. Further-more, deregulation of leptin levels has been correlated with the pathogenesis ofvarious disorders associated with reproduction and gestation, including gestationaldiabetes mellitus (GDM). Due to the relevant incidence of the GDM and theimportance of leptin, we decided to review the latest information available aboutleptin action in normal and GDM pregnancies to support the idea of leptin as animportant factor and/or predictor of diverse disorders associated with reproductionand pregnancy.